Diversidade de Orchidaceae e biossistemática de epidendrum ibaguense Kunt na Serra do Tepequém, Roraima, Brasil - Nóbrega, Sanna Rocha (2017)
The Orchidaceae family is one of the most numerous among the angiosperms, with the genus Neotropical Epidendrum L. showing around 1200 species, with records of morphological variations. In the literature, the occurrence of different floral phenotypes is associated with divergence and suggests reproductive isolation, resulting in speciation. At the Tepequém Mountain, Roraima, E. ibaguense Kunth shows variation in flower coloration. Thus, this study aimed to determine the diversity of Orchidaceae at the Tepequém Mountain, to characterize the morphotypes of E. ibaguense and to determine the morphotypes’ chromosome number. Species of Orchidaceae were photographed and collected between 2013/2015 during expeditions to the study site, resulting in the registration of 20 genera and 34 species, which is equivalent to 10% of Roraima’s Orchidaceae diversity. The phenotypic characterization of E. ibaguense was performed using a sample of 41 individuals marked with PVC plates, with monthly observations. The reproductive system was studied through selfpollination and cross-pollination experiments. The resulting fruit were collected and analyzed for seeds viability. Finally, for the cytogenetic analysis, samples were collected from the radicular apex of the different morphotypes. Samples were pre-treated with 8Hq at 4°C/24h and fixed in Carnoy at 4°C. Later, a conventional method was used for cytogenetics. To determine the chromosome number and nucleos type, slides were photomicrographed. Epidendrum ibaguense showed a flowering period between November and February. Fruit formation rates of 68% and 30% were found for self-pollination and cross-pollination, respectively. Seeds viability of 69% and 80% were found for -pollination and crosspollination, respectively. E. ibaguense was deemed self-compatible for chromosome number through the self-incompatibility index (86.6%); intra and inter-population chromosomal variation was found, with the magenta, pink and white morphotypes showing 2n= 58, while the red morphotypes fluctuated between 2n= 72 and 76. The interphase nuclei were predominantly semi-reticulated in morphotypes 2n = 58 and unreticulated in 2n = 72 and 76. The Tepequém Mountain is an area rich in Orchidaceae species. Among these species, E. ibaguense displays significant morphologic variations among its different morphotypes and variation in chromosome number, indicating the occurrence of speciation in the studied population.